Psi Political Strategy in the Roasting of Muslim Tretants And Coki Pardede Deconstruction Study - Fikri; Muhammad Aldianto Muheldi; Dyta Septiyatik (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
The Indonesian Political Party or abbreviated as PSI is a political party that is new to Indonesian politics world. The emergence of PSI makes a new face, as they consist of young people who are still fresh in Indonesian politics. Along the way, PSI issued controversial statements to attack their political opponents. As a political party, PSI also needs to make a political strategy to get the sympathy of the people to be able to sit on government benches. Through roasting which has another meaning of ridiculing what Tretan Muslim and Coki Pardede did on the sixth anniversary of PSI, there are strategies with hidden meanings in them. Deridda's theory can be used to dismantle the meanings conveyed by Tretan Muslim and Coki Pardede